Theoretical Issues of Analysis and Evaluation of the Activity of Commercial Banks in Uzbekistan - Abdumutalova Gulrukh Shuhratjon's daughter (International Journal on Orange Technologies, 2023)
This article discusses theoretical issues of analysis and assessment of the activity of commercial banks in Uzbekistan. In the article, the author revealed the level of research and analytical methodology of this topic.